Crisis in Myanmar and the responsibility to protect - Hannah Ruth Chia (2016)
Cyclone Nargis has killed an estimated 100,000 people in Myanmar and left some two million people in desperate need of help. It has also laid bare ASEAN and the international community’s continuing inability to deal with the military junta’s stance on any issue, especially one as critical as the prevention of aid and aid workers delivering life saving assistance.